Strategi Kepala MI (Madrasah Ibtidaiyah) Dalam Menarik Minat Calon Peserta Didik Di Distrik Sorong Timur Kota Sorong Tahun Ajaran 2022 - Afroh Nailil Hikmah; Ita Diah Purnama Sari (MISOOL: Jurnal Pendidikan Dasar, 2023)
This research aims to describe and find out: (1) the strategy of the MI head in the East Sorong district of Sorong City in attracting the interest of prospective students; and (2) supporting and inhibiting factors for implementing the MI head's strategy in the East Sorong district of Sorong City in attracting the interest of prospective students. This research uses a qualitative approach with a descriptive type. Data was collected using interviews, observation and documentation. Data were analyzed through the stages of data reduction, data presentation, and drawing conclusions. The validity of data using theoretical triangulation consists of data collection, reduction, data presentation and conclusions. The results of this research show that: (1) The strategy used by the head of MIyang in the East Sorong District of Sorong City to attract the interest of prospective students is planning, organizing, mobilizing or directing and supervising or controlling activities. So that this strategy can have the advantages of each madrasa; and (2) supporting and inhibiting factors for the MI head's strategy, namely improving the quality of madrasas by offering several advantages for each madrasah, namely developing facilities and infrastructure to ensure that the madrasah becomes better and better viewed by the community so that more and more prospective students are interested in registering themselves. at the educational institution